Penerapan Teknologi Administrasi Dalam Knowledge Transfer Guru Di SD Inpres Boyaoge - Anggrini Anggrini; Harnida Wahyuni Adda; Fatlina Zainuddin (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this study is to find out the application of administrative technology in teacher knowledge transfer which will be used as a follow-up to implementing administrative technology and also to find out the development of teachers in completing administration using technology. The method used in an effort to achieve this goal is observation by conducting direct observations in the field to find out what conditions occur what the school needs and what obstacles occur. Through knowledge transfer, some teachers who previously had difficulty using technology, especially laptops, are slowly getting used to it, they are starting to arrange administration using technology and storing files on laptops. This program is expected to provide direct benefits to teachers, especially SD Inpres Boyaoge teachers in increasing knowledge, skills, in completing administration using technology.